USUL-İ FIKIH İLMİ VE AKIL ÜRÜNÜ BİLİMSEL BİR USUL DENEMESİ - Osman Eskicioğlu (İslami İlimler Dergisi)
In this article, it is focused on the contributions that the method of İslamic jurispredence which can be used not only by science of İslamic jurisprudence, but also by other scientific disciplines, may make for constituting a scientific methodology. In the article, the formation of İslamic sciences and the İslamic jurispredence is discussed from the methodology of science perspective. Then moving from the method of İslamic jurisprudence, a new legal methodology approach which can be used in all legal systems is offered.